The Optical System Design of a Space-Based Wide-Field Infrared Slitless Spectrometer - Yue Chen; Liang Zhou; Peiquan Chen; Pengkai Dong; Haiyang Zhang; Wenji She (Photonics)
With the increasingly complex space environment, the operational safety of spacecraft faces severe challenges, creating an urgent need to develop efficient and reliable space target detection and identification technologies. Traditional optical detection equipment faces significant challenges in space target detection and identification due to the low signal-to-noise ratio of space targets. To address the limited field of view (FOV) of traditional spectrometers, this paper proposes an improved wide-FOV infrared slitless spectrometer system based on the Dyson spectrometer. The system consists of three main components: a front telescope system, a spectral dispersion system, and a relay lens system. The front telescope system adopts a Ritchey–Chrétien structure and incorporates a correction lens group to enhance imaging quality. To overcome the practical challenges of conventional Dyson spectrometers—such as the high difficulty and cost in manufacturing and aligning concave gratings—an improved Dyson spectrometer based on a planar blazed grating is designed. A collimating lens group is incorporated to reduce spectral line curvature and chromatic aberration while ensuring a linear spectral dispersion relationship, achieving “spectrum-value unification” in the system. Additionally, a secondary imaging relay lens system is designed to ensure 100% cold stop matching efficiency, thereby minimizing stray light interference. Through optimization and ray tracing using optical design software, the final system achieves a field of view of 0.69° × 0.55°, a spectral resolution of 8.41 nm/pixel, spectral line curvature and chromatic aberration both below 10 µm, and a nearly linear spectral dispersion relationship, realizing spectrum-value unification to facilitate target identification. This infrared slitless spectrometer can stably acquire the spectral characteristics of space targets without requiring high-precision theodolites, providing a novel technical solution for the identification of dynamic space targets. It holds broad application prospects in space surveillance and related fields.